COLLABORATIVE GOVERNANCE DALAM PEMUNGUTAN RETRIBUSI TERMINAL DI TERMINAL TIPE B KOTA DEPOK TAHUN 2022 - Winarsih, Ririn Yulia; Selvi, Selvi (Jurnal Ilmu Administrasi Publik, 2025)
Collaborative Governance is an approach that involves various stakeholders, including local governments, related agencies, the private sector and the community in the process of policy making and implementation. This research aimed to find out how the form of collaborative governance in collecting terminal fees at Type B Terminals in Depok City, especially at the Terminal Management Service Technical Implementation Unit. The research method used was a qualitative approach with data collection techniques through interviews, observation and documentation. The results of this study showed that the implementation of collaborative governance in collecting terminal fees at Type B Terminals in Depok City still faced obstacles such as lack of coordination between stakeholders and varying levels of compliance of transportation service users in the terminal. Despite facing several obstacles, efforts were made to improve the effectiveness of terminal retribution collection such as conducting socialization, increasing transparency in terminal management and improving services, facilities and security at the terminal. This approach has the potential to improve the effectiveness of terminal management and transparency with the cooperation  between local governments, related agencies and the community.